Intraoperative tranexamic acid administration in cranial meningioma surgery: a meta-analysis of prospective randomized, double-blinded, and placebo-controlled trials - Vychopen, Martin; Arlt, Felix; Güresir, Erdem; Wach, Johannes (Frontiers in Oncology, 2024)
ObjectiveCranial meningioma surgeries often involve significant blood loss and transfusions. Tranexamic acid (TXA) has been used to reduce blood loss in various surgeries. This meta-analysis of randomized placebo-controlled trials (RCTs) evaluates the impact of TXA in cranial meningioma surgery.MethodsPubmed, Web of Science, and Cochrane Library were searched for RCTs. Studies were compared for: Blood loss, operative time, hospital stay, reoperation rates, allogeneic and autologous transfusion, and incidence of complications.ResultsSeven RCTs with 490 patients receiving TXA and 491 receiving placebos were included. TXA significantly shortened operative time (Mean Difference (MD): -20.95; 95%CI: -39.94 to -1.95; p=0.03). Blood loss was lower with TXA (MD: -262.7 ml; 95%CI: -397.6 to -127.8; p=0.0001). Odds of reoperation were not significantly different (OR: 0.44; 95%CI: 0.13-1.45; p=0.18). TXA significantly reduced the need for RBC transfusions (OR: 0.47; 95%CI: 0.22-0.99; p<0.05). No significant differences were observed regarding postoperative seizures (OR: 1.06; 95%CI: 0.56-2.03; p=0.85), hydrocephalus (OR: 0.25; 95%CI: 0.03-2.29; p=0.22), or hematoma (OR: 0.52; 95%CI: 0.22-1.28; p=0.16). Hospital stay was shortened in the TXA group (MD: -1.23; 95%CI: -2.41 to -0.05; p=0.04).ConclusionThis meta-analysis suggests that a single intraoperative dose of TXA reduces blood loss, allogeneic blood transfusions and shortens surgery time.